1999
DOI: 10.1086/302287
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Rare Prostate Cancer–Susceptibility Locus at Chromosome 1p36

Abstract: Combining data from a genomic screen in 70 families with a high risk for prostate cancer (PC) with data from candidate-region mapping in these families and an additional 71 families, we have localized a potential hereditary PC-susceptibility locus to chromosome 1p36. Because an excess of cases of primary brain cancer (BC) have been observed in some studies of families with a high risk for PC, and because loss of heterozygosity at 1p36 is frequently observed in BC, we further evaluated 12 families with both a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
174
3
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 285 publications
(188 citation statements)
references
References 43 publications
7
174
3
4
Order By: Relevance
“…Six prostate cancer susceptibility loci (HPC1 at 1q24-25 (Smith et al, 1996), PCAP at 1q42-43 (Berthon et al, 1998), HPCX at Xq27-28 (Xu et al, 1998), CAPB at 1p36 (Gibbs et al, 1999), HPC20 at 20q13 (Berry et al, 2000) and HPC2 at 17p12 (Tavtigian et al, 2001)) and two candidate susceptibility genes (HPC2/ELAC2 at 17q (Tavtigian et al, 2001) and RNASEL at 1q24-25 ) have been reported.…”
mentioning
confidence: 99%
“…Six prostate cancer susceptibility loci (HPC1 at 1q24-25 (Smith et al, 1996), PCAP at 1q42-43 (Berthon et al, 1998), HPCX at Xq27-28 (Xu et al, 1998), CAPB at 1p36 (Gibbs et al, 1999), HPC20 at 20q13 (Berry et al, 2000) and HPC2 at 17p12 (Tavtigian et al, 2001)) and two candidate susceptibility genes (HPC2/ELAC2 at 17q (Tavtigian et al, 2001) and RNASEL at 1q24-25 ) have been reported.…”
mentioning
confidence: 99%
“…In such studies, even verification of the tumor site has been problematic and reliable data on tumor characteristics cannot be obtained. [15][16][17][18][19] The Swedish Family-Cancer Database is unique in this regard because it includes a large proportion of the Swedish population in families starting from 1932 and identifies all cancers in the family members based on the nationwide Swedish Cancer Registry. The Swedish Family-Cancer Database has been updated several times, and familial risks have been published from various versions of it, though without histology-specific data, which will be reported here.…”
mentioning
confidence: 99%
“…Recently, several loci have been implied in predisposing to prostate cancer by genetic linkage studies in cancer families. These include the HPC-1 locus at 1q24-q25 (Smith et al, 1996), HPC2 at 1q42-q43 (Berthon et al, 1998), HPCX at Xq27-q28 (Xu et al, 1998), HPBC at 1p36 (Gibbs et al, 1999), and loci at 20q13 (Berry et al, 2000), 11p (Gibbs et al, 2000) and 16q (Suarez et al, 2000). Exploration of the genetic basis of prostate cancer susceptibility by linkage analysis is challenging due to genetic heterogeneity (the large number of loci involved), due to incomplete penetrance of germline mutations and due to clustering of sporadic prostate cancer.…”
mentioning
confidence: 99%